Homotopy simulation of non-newtonian spriggs fluid flow over a flat plate with oscillating motion - Ray, Atul Kumar; Gorla, Rama Subba Reddy; Vasu, B. (Zielona Góra: Uniwersytet Zielonogórski)
An incompressible flow of a non-Newtonian Spriggs fluid over an unsteady oscillating plate is investigated using the Homotopy Analysis Method (HAM). An analytic solution of sine and cosine oscillations of the plate has been obtained. The similarity transformation is introduced to reduce the governing partial differential equations into a single non-linear dimensionless partial differential equation.
Keywords: incompressible flow; oscillatory plate; Stokes` second problem; HAM; non-Newtonian Spriggs fluid